I RESPECT YOU AND I HELP YOU : LINKS BETWEEN POSITIVE RELATIONSHIPS AT WORK AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Peyrat-Guillard, Dominique; Glinska-Neweś, Aldona (Journal of Positive Management, 2014)
The main purpose of this article is to present links identified among manifestations of employee positive relationships and organizational citizenship behaviour. The presentation is based on the results collected through a questionnaire survey conducted in Polish companies. The data analysis shows particular associations between positive relationships and organisational citizenship behaviour (OCB). Our results suggest that OCB-I (the behaviours targeted toward other individuals in an organisation) may be triggered by respect and acceptance and that OCB-O (i.e. the behaviours targeted toward an organisation itself) may be considered as effects of the relationships manifesting honesty and reliability. We suggest research avenues to capture the processes behind the described associations.